Synergetic of Pt Nanoparticles and H-ZSM-5 Zeolites for Efficient CO2 Activation: Role of Interfacial Sites in High Activity - Sápi, András; Kashaboina, Upendar; Ábrahámné, Kornélia B.; Gómez-Pérez, Juan Fernando; Szenti, Imre; Halasi, Gyula; Kiss, János; Nagy, Balázs; Varga, Tamás; Kukovecz, Ákos; Kónya, Zoltán (Frontiers in Materials, 2019)
Catalytic systems prepared by controlled processes play an important role in the utilization of CO2 via catalytic hydrogenation to produce useful C1 chemicals (such as CO, CH4 and CH3OH), which will be vital for forthcoming applications in energy conversion and storage. Size controlled Pt nanoparticles were prepared by a polyol method and deposited on H-ZSM-5 (SiO2/Al2O3 = 30, 50, 80 and 280) zeolite supports. The prepared catalysts were tested for the CO2 hydrogenation in the temperature range of T = 473–873 K and ambient pressure, with CO2/H2 = 1:4. Size-controlled Pt nanoparticles boosted the catalytic activity of the pure H-ZSM-5 zeolites resulted in ~16 times higher CO2 consumption rate. The activity were ~4 times higher and CH4 selectivity at 873 K was ~12 times higher over 0.5 % Pt/ H-ZSM-5 (SiO2/Al2O3 = 30) compared to 0.5 % Pt/H-ZSM-5 (SiO2/Al2O3 = 280). In situ DRIFTS studies assuming the presence of a surface comlex in which the CO is perturbed by hydrogen and adsorbes via C-end on Pt but the oxygen tilts to the protons of the zeolite support.